Foxg1 Overexpression in Neocortical Pyramids Stimulates Dendrite Elongation Via Hes1 and pCreb1 Upregulation - Chiola, Simone; Do, Mihn Duc; Centrone, Lucy; Mallamaci, Antonello (Cerebral cortex (New York, N.Y. 1991), 2019)
Abstract The architecture of neocortical projection neurons is subject of a complex gene control. Here we demonstrated that Foxg1, a transcription factor gene which patterns the early rostral brain and sets the pace of telencephalic neuronogenesis, specifically stimulates dendrite elongation. This phenomenon occurs in vivo like in vitro, and it is detectable even upon moderate changes of Foxg1 expression levels. We found that Foxg1 acts by stimulating Hes1, which in turn upregulates pCreb1, a well-known pro-dendritogenic effector, and downregulates Syt and Ndr1, namely two established antagonizers of dendrite elongation. Moreover, Foxg1-driven pCreb1 upregulation requires PKA and AKT, and correlates with reduced PP1 and PP2A phosphatase activity. These findings contribute to clarify normal neurodevelopmental and activity-related regulation of neuritogenesis. They further suggest that an abnormal sizing of the dendritic tree of neocortical projection neurons may occur in West and Rett syndrome patients with anomalous FOXG1 allele dosages and contribute to their neurolopathological profiles.